DETERMINASI PROFITABILITY DAN FIRM VALUE SUB SEKTOR INDUSTRI MAKANAN DAN MINUMAN - Suhardjo Suhardjo; Nicholas Renaldo; Suyono Suyono; Nyoto Nyoto; Siti Ngatikoh (Kurs : Jurnal Akuntansi, Kewirausahaan dan Bisnis, 2022)
The phenomenon of the food and beverage industry affected by COVID-19 is a challenging issue to be studied and analyzed in Indonesia where this industry is one of the priorities for the implementation of industry 4.0 and a source of Indonesia's economic growth until 2030. This study aims to test the determination of profitability and firm value of the consumer goods industry. food and beverage industry sub-sectors listed on the Indonesia Stock Exchange in 2016– 2020. The analysis uses multiple linear regression with Smart PLS tools and the sample used is purposive sampling technique on 16 consumer goods industrial companies in the food and beverage industry sub-sector listed on the IDX. 2020. The results show that liquidity has a positive and significant effect on profitability, capital structure has a negative and significant effect on profitability, liquidity has a negative and insignificant effect on firm value, capital structure has a negative and significant impact on profitability. significant effect on firm value, and profitability has a positive and insignificant effect on firm value. Future research develops investment variables of fixed assets, dividends, retained earnings policy, technological innovation related to efficiency, application of green activity. And use macroeconomic assumptions such as: consumption spending, investment, government spending, exports and imports as well as inflation, money supply, interest rates. Fenomena industri makanan dan minuman yang terdampak covid 19 menjadi isu yang menantang untuk dikaji dan dianalisa di Indonesia dimana industri ini menjadi salah satu prioritas penerapan industry 4.0 dan sumber pertumbuhan ekonomi Indonesia hingga 2030. Penelitian ini bertujuan untuk menguji determinasi profitability dan firm value industri barang konsumsi sub sektor industri makanan dan minuman yang terdaftar di Bursa Efek Indonesia tahun 2016 – 2020. Analisa menggunakan regresi linier berganda dengan tools Smart PLS dan sampel yang digunakan dengan teknik purposive sampling terhadap 16 perusahaan industri barang konsumsi sub sektor industri makanan dan minuman yang terdaftar di BEI tahun 2020. Hasil penelitian menunjukan bahwa likuidity berpengaruh positif dan signifikan terhadap profitability, capital structure berpengaruh negatif dan signifikan terhadap profitability, liquidity berpengaruh negatif dan tidak signifikan terhadap firm value, capital structure berpengaruh negatif dan signifikan terhadap firm value, dan profitability berpengaruh positif dan tidak signifikan terhadap firm value. Future reseach mengembangkan variabel investasi aktiva tetap, deviden, kebijakan laba ditahan, innovasi teknologi terkait efisiensi, penerapan green activity. Dan penggunakan asumsi-asumsi makro ekonomi seperti seperti : pengeluaran konsumsi, investasi, pengeluaran pemerintah, ekspor dan impor serta inflasi, jumlah uang beredar, tingkat suku bunga.